Analysis of LCL Filter Topologies for DC-DC Isolated Cuk Converter at CCM Operation - Erdal Sehirli (IEEE Access, 2022)
In this study, the application and analysis of LCL filter topologies including an LCL, an LCL with damping, and an LCL trap filter used by a DC-DC isolated Ćuk converter operated at CCM are presented. The converter is designed for 50 W with 42 kHz switching frequency using a SiC MOSFET as a power switch. Although LCL filter topologies are commonly used with an inverter, their use in DC-DC converters has not been studied in detail. The main contribution of the paper is the application, design, and analysis of an LCL trap filter, which is not presented for a DC-DC converter in the literature, as an input filter of a DC-DC isolated Ćuk converter. For exact analysis of the effect of the filter, as a second main contribution of the paper, a state-space average mathematical model, small signal analysis of an isolated Ćuk converter for CCM operation, which was not presented before in the literature, is derived and its transfer function is obtained. In this paper, the practical design and transfer functions of LCL-based filter topologies are also presented. In order to analyze the effect of filter topologies by using linear methods including root locus and Bode graphs, the transfer function of the converter is cascaded with the transfer function of each filter separately, which is the third contribution of the paper because such analysis has not been presented in the literature. Furthermore, each cascaded transfer function and the transfer function of the converter are validated by step responses. All LCL filters, with an LC filter for comparison, are employed in the experimental setup. Owing to the applications, control characteristics and input current ripples are measured. In addition, the efficiencies of each different structure are determined. As a result of the analysis and measurements, the LCL trap filter gives better results in terms of efficiency (86%) and input current ripple (0.96 A peak). Moreover, the LCL with damping filter gives poorer control characteristics, but the maximum gain of the controller avoiding the instability of LCL with damping is 0.0855, which is higher than that of the others. Furthermore, it is shown that each LCL filter topology provides a 45% lower total inductor value compared to the LC filter.